Periodontal health in shortened dental arches: A 10-year RCT. Issue 4 (October 2020) - Walter, Michael H.; Dreyhaupt, Jens; Mundt, Torsten; Kohal, Ralf; Kern, Matthias; Rauch, Angelika; Nothdurft, Frank; Hartmann, Sinsa; Böning, Klaus; Boldt, Julian; Stark, Helmut; Edelhoff, Daniel; et al.
Abstract: Purpose: This analysis focused on periodontal health in shortened dental arches (SDAs). Methods: In a randomized controlled clinical trial, patients with missing molars in one jaw and at least one premolar and canine on both sides were eligible for participation. In the partial removable dental prosthesis (PRDP) group ( n = 79), molars were replaced with a precision attachment retained PRDP. In the SDA group ( n = = 71), the SDA up to the second premolars was either left as is or restored with fixed dental prostheses. Outcome variables were vertical clinical attachment loss (CAL-V), pocket probing depth (PPD), bleeding on probing (BOP) and plaque index (PLI). For CAL-V and PPD, the changes at six measuring points per tooth were analyzed. For BOP and PLI, patient related rates were calculated for each point in time. Statistical methods included linear regression analyses. Results: In the intention-to-treat (ITT) analysis for CAL-V in the study jaw, the 10 year patient related mean changes were 0.66 mm in the PRDP group and −0.13 mm in the SDA group. The resulting mean patient related group difference of 0.79 mm (95% CI: 0.20 mm–1.38 mm) was significant ( p = 0.01). There were no significant differences in the ITT analyses for PPD. For BOP and PLI, significant group differences with more favorable results for the SDA group were found. Conclusions: In view of lacking substantial differences for CAL-V and PPD, the overall differences were considered of minor clinical relevance. The results add confirmatory evidence to the shortened dental arch concept and its clinical viability (controlled-trials.com ISRCTN97265367).